Impact Of Coffeine Consumption on Sleep Quality and Mental Health Of Collage Student - Mokhamad Nurhadi; Suwarningsih; Asni Hasanuddin; La Ode Asrianto (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the impact of caffeine consumption on sleep quality and mental health of students. Caffeine consumption has become a common habit among college students, especially to combat fatigue and increase alertness when facing high academic demands. However, excessive caffeine consumption can risk impairing sleep quality and contributing to mental health problems such as anxiety and depression. This study uses a quantitative approach with a cross-sectional survey design, involving 230 students as randomly selected respondents from various universities in Indonesia. Data were collected through questionnaires that measured caffeine consumption frequency, sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and anxiety and depression levels using Generalized Anxiety Disorder (GAD-7) and Patient Health Questionnaire-9 (PHQ-9). The results of the analysis showed that high caffeine consumption was associated with decreased sleep quality and increased symptoms of anxiety and depression in college students. The study suggests the need for better management of caffeine consumption among college students to support better physical and mental health.